2021
DOI: 10.1021/acschemneuro.0c00787
|View full text |Cite
|
Sign up to set email alerts
|

Phoenixin-20 Prevents ox-LDL-Induced Attachment of Monocytes to Human Aortic Endothelial Cells (HAECs): A Protective Implication in Atherosclerosis

Abstract: Background: The cause of atherosclerosis is not known, and therefore the current treatment options are limited. In the present study, we aimed to investigate the effects of Phoenixin 20 and its receptor G protein-coupled receptor 173 (GPR173) against ox-LDL-induced endothelial dysfunction.Materials and Methods: Human aortic endothelial cells (HAECs) were treated with 10 μg/ml ox-LDL in the presence or absence of phoenixin 20. Gene expression of GPR173, ICAM-1, VCAM-1, IL-1β, IL-8, MCP-1, and NOX-4 were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Endothelium plays an important role in pathogenesis of many diseases and cardiovascular problems such as atherosclerosis and HT 21 . Wei et al reported that GPR173 agonism by PNX-20 plays a protective role against ox-LDL-induced endothelial dysfunction 13 . VSMCs are major components of the vascular wall and serve to mediate hemodynamic vessel functions, playing a crucial role in regulating blood pressure in physiological conditions and HT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelium plays an important role in pathogenesis of many diseases and cardiovascular problems such as atherosclerosis and HT 21 . Wei et al reported that GPR173 agonism by PNX-20 plays a protective role against ox-LDL-induced endothelial dysfunction 13 . VSMCs are major components of the vascular wall and serve to mediate hemodynamic vessel functions, playing a crucial role in regulating blood pressure in physiological conditions and HT.…”
Section: Discussionmentioning
confidence: 99%
“…PNX-14 has been reported to regulate proliferation and apoptosis of vascular smooth muscle cells (VSMCs) 12 . GPR173 agonism by PNX-20 plays a protective role against ox-LDL-induced endothelial dysfunction 13 . Based on these data, this study was designed to evaluate serum concentrations of PNX-14 and PNX-20 in HT patients and healthy controls and the clinical value of these peptides as novel biomarkers for HT.…”
Section: Introductionmentioning
confidence: 99%
“…Phoenixin-20 inhibited LPS-induced inflammation of dental pulp cells, and phoenixin-20 inhibited the release of pro-inflammatory cytokines and inflammatory mediators induced by LPS, including monocyte chemotactic protein-1 (MCP-1), IL-6, intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), MMP-2 and MMP-9 ( Sun, et al, 2020 ). Phoenixin-20, activating GPR173, significantly ameliorated oxidized low-density lipoprotein (ox-LDL) induced harmful effects by suppressing the NF-κB pathway in human aortic endothelial cells, and the harmful effects were presented as an increase in ROS, NOX-4, IL-1β, interleukin-8 (IL-8), and MCP-1 expression, as well as ICAM-1 and VCAM-1 release ( Wei et al, 2021 ). Recently, Zandeh-Rahimi et al found that phoenixin-14 could protect indomethacin-induced duodenal ulcer in rats, and phoenixin-14 exhibited a decrease in serum levels of inflammatory cytokines (IL-1β, TNF-α, IL-6, and IL-12), malondialdehyde and myeloperoxidase activity, and an increase on SOD and catalase activity in duodenal ulcer ( Zandeh-Rahimi et al, 2022 ).…”
Section: Function Of Phoenixinmentioning
confidence: 99%
“…In atherosclerosis, GPR173 expression is reduced in human aortic endothelial cells upon exposure to oxidized low-density lipoprotein, thereby implying a role for PNX in disease onset. Moreover, PNX-20 agonism can improve disease progression by preventing the attachment of THP-1 monocytes to human aortic endothelial cells and attenuating the NF-κB pathway [ 51 ].…”
Section: Inflammationmentioning
confidence: 99%